2018
DOI: 10.20318/recs.2018.4495
|View full text |Cite
|
Sign up to set email alerts
|

Newspaper portrayal of mental illness in England, Canada, Portugal, Spain and Japan = Representación de las enfermedades mentales en periódicos de Inglaterra, Canadá, Portugal, España y Japón

Abstract: Research concerning media portrayals of mental illnesses and the effects such portrayals might have on the public has usually been carried out within one country as a geographical limit. Herein, we analyse the results of the research carried out through the analysis of newspapers in 5 different disperse countries around the world in the last decade; England, Canada, Portugal, Spain and Japan. Some of these countries have started national campaigns to reduce the stigmatisation of these conditions, including a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In this respect, prior research has shown that media outlets (e.g. news, entertainment) contribute to perpetuate stereotypical portrayals of mental illnesses, associating these with dangerousness, violence and crime (Nawková et al, 2012;Stuart, 2006;Vengut Climent, 2018). The stigma discourse in our sample suggests that users' negative tweets are ideologically charged and revolve around socio-cultural practices (e.g.…”
Section: Main Findingsmentioning
confidence: 70%
“…In this respect, prior research has shown that media outlets (e.g. news, entertainment) contribute to perpetuate stereotypical portrayals of mental illnesses, associating these with dangerousness, violence and crime (Nawková et al, 2012;Stuart, 2006;Vengut Climent, 2018). The stigma discourse in our sample suggests that users' negative tweets are ideologically charged and revolve around socio-cultural practices (e.g.…”
Section: Main Findingsmentioning
confidence: 70%